Preliminary estimates of whaling-induced mortality in the 19th century North Pacific right whale (Eubalaena japonicus) fishery, adjusting for struck-but-lost whales and non-American whaling - Scarff, James E. (J. Cetacean Res. Manage., 2020)
This study develops preliminary estimates of total whaling-induced mortality of northern right whales in the 19th century North Pacific pelagic whale fishery. Best’s (1987) study of American whaling returns resulted in estimates of the total American catch of 14,480 and 15,374 northern right whales during the period 1839-1909. The present study offers adjustment factors to estimate total mortality from these catch data. Quantitative data from 14 pelagic expeditions for northern right whales in the North Pacific from 1838-1860 and additional anecdotal information about struck-but-lost animals is reviewed. On 12 voyages, 327 northern right whales were struck with harpoons, but only 133 landed. Adjusted for the subsequent recovery of struck whales, this implies a ratio of 2.43 whales struck for each whale eventually secured and flensed by whaleships. Data from four voyages show that of 148 northern right whales struck with harpoons, 14 sank before they could be processed. From a sample of five voyages, 80 northern right whales were landed and 31 carcasses sank without being secured. During the height of pelagic whaling in the North Pacific, approximately 10% of the fleet was non-American, primarily French. Adjusting recorded catch estimates for struck-but-lost mortality and non-American whaling yields preliminary estimates of total mortality in this fishery in the range of 26,500-37,000 animals during the period 1839-1909. In the single decade of 1840-49, between 21,000-30,000 northern right whales may have been killed in the North Pacific, Sea of Okhotsk and Bering Sea, representing about 80% of the northern right whales killed in this region during the period 1839-1909.